Improvisation of Project Based Learning With Combination of Collaborative Learning as Rapid Response to Pandemic Learning - Soetam Rizky Wicaksono; M. Syukri Azwar Lubis; Edy Suprapto; Khasanah Khasanah; Almira Ulimaz (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The Covid-19 pandemic caused the effects of learning activities from home. The phenomenon requires improvisation as a quick response so that the teaching and learning process continues to run and maintains learning motivation, especially in the scope of college. Activities that are assumed to be able to maintain motivation online is to provide tasks in the form of projects or Project Based Learning (PBL) which in this context does not mean eliminating face-to-face activities offline, but in the sense of providing sustainable projects in one semester and staying connected to lecture materials. This PBL is combined with Collaborative Learning (CL) in order to conduct a continuous project review. This research was conducted in Ma Chung University's Information Systems study program for Programming Language courses. The results of this implementation are evaluated by conducting FGD (Focus Group Discussion) in two stages. In the first stage there are some shortcomings that are then corrected by adding the obligation to upload the project to Github and intensify the involvement of lecturers. So in the second stage, FGD results show improved results. The results of the study are generic prescriptions, namely: the implementation of PBL accompanied by a mature plan and preparation, improvisation of PBL accompanied by the application of CL accompanied by the role of lecturers as facilitators need to be evaluated gradually, and the implementation of online collaboration can be applied because students can quickly adapt online. Keywords: Project Based Learning, Collaborative Learning, Response Pandemic Learning